Sintesis dan Uji Aktivitas Antibakteri Senyawa N-fenil-4-klorobenzamida - Elok Dea Orens Ubung Wisnu; Indah Purnama Sary; Dwi Koko Pratoko (Pustaka Kesehatan, 2018)
N-phenylbenzamide is benzamide derivatives, which is potential as an antibacterial agent. N-phenyl-4-chlorobenzamide is N-phenylbenzamide derivative that substitued by chloro to the para position and it was expected to enhance the antibacterial activity. N-phenyl-4-chlorobenzamide was synthesized by reacting 1,3-diphenyilthiourea and 4-chlorobenzoil chloride. This compound has been purified and provided 53% of product with crystal shape, white color, and melting point of 195-197 oC. The purification of this compound was confirmed by TLC and the structure was identified by 1H-NMR, 13C-NMR, and FTIR spectroscopy. This compound was tested for its activity against gram positive bacteria Staphylococcus aureus and gram negative bacteria Pseudomonas aeruginosa, evaluated by well diffusion method and the result showed no activity against both Staphylococcus aureus and Pseudomonas aeruginosa. Keywords: N-phenyl-4-chlorobenzamide, synthesis, antibacterial activity